2016
DOI: 10.1093/geronb/gbw027
|View full text |Cite
|
Sign up to set email alerts
|

Work Impact and Emotional Stress Among Informal Caregivers for Older Adults

Abstract: These findings suggest the need to further explore work among informal caregivers and associations with emotional stress, as well as consider work-based policy approaches, organizational and/or societal, to support informal caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 32 publications
(49 reference statements)
5
73
0
6
Order By: Relevance
“…Among working‐age family caregivers accessing the Older Americans Act's National Family Caregiver Support Program, nearly 40% of nonworking family caregivers reported quitting their jobs or retiring early from work because of intensive caregiving demands. The majority of nonworking caregivers were women who provided help with three or more activities of daily living (such as bathing or feeding) for a spouse and who experienced high emotional stress …”
Section: Caregiving's Impact On Employment and Financial Well‐beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Among working‐age family caregivers accessing the Older Americans Act's National Family Caregiver Support Program, nearly 40% of nonworking family caregivers reported quitting their jobs or retiring early from work because of intensive caregiving demands. The majority of nonworking caregivers were women who provided help with three or more activities of daily living (such as bathing or feeding) for a spouse and who experienced high emotional stress …”
Section: Caregiving's Impact On Employment and Financial Well‐beingmentioning
confidence: 99%
“…The majority of nonworking caregivers were women who provided help with three or more activities of daily living (such as bathing or feeding) for a spouse and who experienced high emotional stress. 10 The economic consequences of reducing work hours, quitting a job to provide care, or taking an unplanned early retirement can be significant. Although available research on the economic effects of family caregiving is limited and largely based on self-reported data, studies show that family caregivers who disrupt their careers or leave the labor force entirely to meet full-time caregiving demands can face substantial economic risk and short-and long-term financial consequences.…”
Section: Caregiving's Impact On Employment and Financial Well-beingmentioning
confidence: 99%
“…The same association was not observed among caregivers who were not working. Further, Longacre et al (2016) also found that working caregivers experience greater emotional stress as the duration of care increases (both in terms of the hours of care provided and the total time spent in the caregiving role), suggesting that the burden of caregiving is cumulative over time for those with work demands.…”
Section: Introductionmentioning
confidence: 95%
“…Working caregivers may also experience concurrent or conflicting work and caregiving demands being made of scarce time and resources, resulting in role strain or conflict at the caregiving-work nexus (Given, Given, Sherwood, & DeVoss, 2013; Gordon, Pruchno, Wilson-Genderson, Murphy, & Rose, 2012). In general, working family caregivers seem more likely to have worse mental health compared to individuals who only work or provide care exclusively (Honda, Date, Abe, Aoyagi, & Honda, 2014; Lee, Walker, & Shoup, 2001; Longacre, Valdmanis, Handorf, & Fang, 2016), especially with regard to depressive symptoms. For example, those engaged both in work and caregiving roles exhibit more depressive symptoms than those involved in only one of those roles (Lee et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Women, who traditionally have taken the role of caregivers, are currently combining this role with work and other responsibilities, which places them under high levels of stress. 23 In Chile, as in many other countries, social views on aging and older age are composed of stereotypes associated with biological decline, the loss of cognitive abilities, and the severe difficulties of older people to adapt to the pace of modern daily life. Currently, almost three out of four Chileans (72.9%) think that senior adults cannot manage by themselves.…”
Section: Aging and Social Conditionsmentioning
confidence: 99%